TECHNICAL KNOWLEDGE AND SCIENCES IN THE CONTEXT OF THE INDUSTRIAL REVOLUTION: METHODOLOGICAL ASPECT - Онопрієнко, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
There are examined the specificity of interaction between science and technique in a period of the industrial revolution in Europe in XVIII and early XIX centuries, formation of such organizational form of production and application of scientific and technical knowledge activity as a specialized laboratory, origins, institualization and differentiation of engineering sciences.